O tratamento criminal dos discursos de ódio publicados em redes sociais: um panorama conceitual e legal sobre condutas odientas e as respostas das cortes de vértice do Brasil - Sonnenstrahl Filho, Charles Moraes (2019)
Humanity's seek for knowledge has allowed us to conclude that, regardless of differences, all individuals belong to the same species, so that all are worthy of the same respect and dignity. Despite the theoretical construction in favor of respect for all there are numerous discriminatory practices, stands out the Universal Declaration of Human Rights, internationally, and nationally, the enactment of 1988 Constitution, until current days. Even worse than hate speeches are, since they are intended to violate the dignity of human groups with particular characteristics and to spread fear and terror, as they boost violence against the victim group. Hateful practices are nothing new, but they take on new shape with their spread on the Internet, especially on social networks, due to their ability to diffusely reach victims and attract followers. Faced with this situation, it is necessary that the State, by means of Criminal Law, represses such conducts. Thus, it is pertinent to question: if we consider the main international treaties and the doctrine, what are the limits on the understanding of hate speech as a constitutive criminal offense and to what extent do they contrast (or not) with the jurisprudence reality of the Supreme Courts of Brazil? This dissertation delves into to answer this question. A concept and different classifications of hate speech were unraveled, distinguishing it from prejudiced speech. It was verified that hate speech is not included in the sphere of protection of the right to freedom of opinion and expression and besides, in Brazil, there is no criminal type that criminalizes, specifically, the issuance of hate speech, but it is possible to punish some of its manifestations through the crime of incitement and apology for the crime. Finally, it was concluded, when investigating the criminal jurisprudence of the Supreme Courts of Brazil, which, until the present, there is no trial where they have faced in depth issues related to the criminal illegality of hate speech published on social networks. As for the basic theory, the analytical theory is used. As for the primary approach method, we used the deductive. As for the secondary approach methods (procedural methods), monograph and statistic were chosen. Finally, as for the research techniques, we operated with the documentary and the bibliographic, as well as direct observation, systematic, non-participatory and individual. The dissertation was divided into two chapters.